Gonadectomy in Raccoons: Anesthetic and Cardiorespiratory Effects of Two Ketamine-Based Pre-Anesthetic Protocols before Sevoflurane-Sufentanil - Sara Nannarone; Valentina De Monte; Rolando Arcelli; Laura Menchetti; Rodolfo Gialletti (Animals, 2020)
Nineteen raccoons were enrolled in this study. The aim was to evaluate and compare the quality of anesthesia and the cardiorespiratory effects following treatment with a ketamine-based combination with either dexmedetomidine (KD group) or midazolam (KM group) in raccoons undergoing ovariohysterectomy/orchiectomy. General anesthesia was maintained with sevoflurane in oxygen and sufentanil infusion. The time required to approach the animals was similar among groups resulting in a median of 5 min after IM injection. Animals in group KD were scored with greater myorelaxation (p < 0.01) and easier intubation (p < 0.05). Moreover 70% of them did not require other drugs for tracheal intubation unlike animals in group KM, which required propofol in 100% of cases. After intubation and connection to the breathing circuit, physiological parameters were monitored continuously and recorded every 5 min. Sevoflurane requirements were lower in group KD than KM (p = 0.005). Blood pressure was maintained within physiological ranges in both groups but with higher values in group KM (p < 0.05). Mild respiratory depression occurred during surgery and animals in group KM showed greater respiratory acidosis (p < 0.05). Recovery was smooth and uneventful in all animals. Both anesthetic protocols can be recommended for safe anesthesia in wild raccoons.